The Impact of Environmental and Behavioral Factors on the Incidence of Dengue Hemorrhagic Fever in Indonesia: Meta-analysis - Muhamad, Fadel T.; Azizah, R. (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Cases of dengue fever in Indonesia will increase to 143,000 by the end of 2022. The aim of the research is to examine the impact of environmental and behavioral factors on the incidence of dengue hemorrhagic fever in Indonesia. This research uses the Meta-Analysis Method with PICOS technology. Some sources of information used include Google Scholar, Research Gate, and Plos ONE, with the help of keywords such as "Environmental factors" and "Behavior." 193 articles were obtained, 151 articles came from Google Scholar, 37 articles from Research Gate, and 5 articles from Plos ONE. The articles obtained were filtered using inclusion criteria such as articles that had a 2x2 table, and discussed dengue fever and behavior with the number of selected articles being 21. At the screening stage, researchers used a cross-sectional research design. JASP application version 0.16.3.0 was used to process meta-analysis data. The key findings show that the habit of hanging clothes has a 2.386 higher risk as a cause of dengue hemorrhagic fever, with the pooled OR value as follows e0.87 = 2.386 (CI 95% 0.17-1.57). The presence of larvae has a risk of 2.075 for dengue fever with the following pooled value e0.73 = 2.075 (CI 95% 0.12-1.33). Meanwhile, the 3 M movement has a risk of 0.406 for the incidence of dengue fever with the following pooled value e-0.90 = 0.406 (CI 95% -1.66-0.15). the conclusion is There is an influence of the habit of hanging clothes, the presence of larvae and the 3M movement on the incidence of dengue hemorrhagic fever.